2020
DOI: 10.1097/corr.0000000000001142
|View full text |Cite
|
Sign up to set email alerts
|

Does an Antimicrobial Incision Drape Prevent Intraoperative Contamination? A Randomized Controlled Trial of 1187 Patients

Abstract: Background The risk of periprosthetic joint infection (PJI), a serious complication after arthroplasty, has not changed for years. Interventions such as eradication of Staphylococcus aureus and antibiotic bone cement are used to diminish infection risk but despite these efforts, the percentage of infection in TKA remains constant. Antimicrobial drapes have a dual action, acting both as a physical and antimicrobial barrier to counter bacterial contamination of the surgical wound. To study the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…The contamination rate of 12% is within the range found in similar studies (Byrne et al 2007 , Font-Vizcarra et al 2011 , Frank et al 2011 , Lindeque et al 2014 ) and in between the 10% (use of antimicrobial drape) and 15% (no use of antimicrobial drape) found in the study by Hesselvig et al ( 2020 ) (for 363 of the 714 included patients antimicrobial drapes were used). Average age and sex distribution of included patients were comparable to those reported in the Danish Knee Arthroplasty Register (DKR), which has a completion rate of 95%.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The contamination rate of 12% is within the range found in similar studies (Byrne et al 2007 , Font-Vizcarra et al 2011 , Frank et al 2011 , Lindeque et al 2014 ) and in between the 10% (use of antimicrobial drape) and 15% (no use of antimicrobial drape) found in the study by Hesselvig et al ( 2020 ) (for 363 of the 714 included patients antimicrobial drapes were used). Average age and sex distribution of included patients were comparable to those reported in the Danish Knee Arthroplasty Register (DKR), which has a completion rate of 95%.…”
Section: Discussionsupporting
confidence: 82%
“…The study design was according to STROBE guidelines. This prospective cohort study combines data from 2 prospective multicenter studies, ICON (Hesselvig et al 2020 ) and SPARK (Mørup-Petersen et al, personal communication). These 2 studies enrolled patients from multiple hospitals over a 2-year period (2016–2018) with a partially shared patient cohort.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the nine included studies that compared the use of iodine-impregnated surgical incise drapes to other practices, five reported decreased rates of SSIs with their use compared with groups of patients in which surgical incise drapes were not used. 19,35,[118][119][120] In one study, it was found that clear plastic adhesive incise drapes increased the risk of SSIs while iodine-impregnated alternatives did not have this effect. 121 Two studies found equivalent SSI rates between patients who received no incise drapes, 122,123 and one study reported similar rates between iodine-impregnated and clear plastic adhesive drapes (see ►Table 4).…”
Section: Surgical Incise Drapingmentioning
confidence: 99%